Applications of psychological skills training for Paralympic table tennis athletes - Lim, T.-H.; Jang, C.-Y.; O`Sullivan, D.; Oh, H. (Journal of Exercise Rehabilitation, 2018)
This study examined effects of psychological skills training (PST) for Korean national table tennis athletes with spinal cord injuries (SCI), who were training for the 2012 London Paralympics. Participants were three male table tennis players with level two SCI, and all participants attended a total of eight sessions of PST over a period of 3 months. The PST consisted of self-talk, imagery, cognitive reconstructing, and routine. To examine the effectiveness of mental coaching, the Test of Performance Strategies questionnaire was administered over three different periods of time: pre-PST, post-PST, and postcompetition. Pre- and posttest outcomes indicated that there were positive changes in self-talk, emotional control, and goal setting of athletes with SCI. With the exception of relaxation, Athlete 1 was able to maintain and use all of the improved mental skills in Paralympic competitions. However, although the mental skills of the athletes 2 and 3 generally improved, they were not able to take full advantage of these improvements in Paralympic competitions. PST can be developed and effectively utilized by athletes with SCI. Disability-specific issues should be considered to provide a better intervention program.